2018
DOI: 10.1111/jen.12556
|View full text |Cite
|
Sign up to set email alerts
|

Floral resources to enhance the potential of the parasitoid Aphidius colemani for biological control of the aphid Myzus persicae

Abstract: Flowering plants have been widely used to enhance biological control. However, this approach has been limited to some extent by the lack of suitable flowering plant species of wide applicability, particularly for global pests. A key example is the green peach aphid, Myzus persicae (GPA). It is commonly attacked by the polyphagous koinobiont aphidiidae, Aphidius colemani, which is also of global occurrence. Here, eight flowering plants were evaluated for the potential enhancement of GPA biological control using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Spontaneous flora within and near the orchards may be also important for these parasitoids’ survival, by providing them with alternative hosts, food and refuge, particularly during winter [68,69,70,71,72]. Consistent with this theory, laboratory experiments have confirmed that Aphidinae improve their fitness when flowers are available [73,74].…”
Section: Discussionmentioning
confidence: 98%
“…Spontaneous flora within and near the orchards may be also important for these parasitoids’ survival, by providing them with alternative hosts, food and refuge, particularly during winter [68,69,70,71,72]. Consistent with this theory, laboratory experiments have confirmed that Aphidinae improve their fitness when flowers are available [73,74].…”
Section: Discussionmentioning
confidence: 98%
“…Sinapis alba has also been shown to increase the longevity and fecundity of the aphid parasitoid A. colemani (Jado et al 2018). In the presence of S. alba flowers, parasitism of M. persicae by A. colemani increased (Jado et al 2018). Sinapis alba did not significantly increase the longevity of Micrococtonus hyperodae Loan (Hymenoptera: Braconidae), a parasitoid of the Argentine stem weevil, Listronotus bonariensis Kuschel (Coleoptera: Curculionidae) (Vattala et al 2006).…”
Section: Lobularia Maritimamentioning
confidence: 99%
“…Compared to other insectary plants, L. maritima stays in bloom for a long time and it attracts less bees that can outcompete hoverflies (Picó and Retana 2001, Ambrosino et al 2006, Hogg et al 2011a. Sinapis alba has also been shown to increase the longevity and fecundity of the aphid parasitoid A. colemani (Jado et al 2018). In the presence of S. alba flowers, parasitism of M. persicae by A. colemani increased (Jado et al 2018).…”
Section: Lobularia Maritimamentioning
confidence: 99%
“…The fact that A. colemani was the only primary parasitoid detected in the field indicates that it is the most immediate candidate for aphid control in these smallholder systems and suggests that biological control of aphids here should thus focus on providing resources that support high A. colemani abundance year-round. This could particularly include food (nectar) resources: Previous studies identified plants including Fagopyrun esculentum , Salvia apiana , Lantana camara , and Conium maculatum as having positive effects on parasitoid longevity and parasitism rates [51,52]. However, these plant species are non-native in northern Tanzania and, as such, are unsuitable for promotion in smallholder East African farming systems, and there has not been sufficient research into the effect they may have on the other trophic levels within these ecosystems.…”
Section: Discussionmentioning
confidence: 99%